2020
DOI: 10.1111/ajo.13220
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Apgar scores and children’s educational outcomes at eight years of age

Abstract: Background Low Apgar scores are associated with neonatal morbidity and mortality, but effects of Apgar scores of 0–5, 6, 7, 8 and 9 (compared with 10) on longer‐term neurodevelopmental outcomes are less clear. Aim To examine the associations between Apgar scores of 0–5, 6, 7, 8 and 9 (compared with 10) and children’s educational outcomes as measured by the Australian National Assessment Program—Literacy and Numeracy (NAPLAN) tests at age eight. Materials and Methods We merged perinatal data including all child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…The Apgar score was originally intended to assess the condition of newborns immediately after birth and to measure the response to resuscitations [ 3 ]. However, the Apgar score, particularly the five-minute Apgar score, is often used in outcome studies, as it provides useful clinical information about the fetal-to-neonatal transition [ 4 , 5 , 6 ], although some professional associations, such as the American Academy of Pediatrics and the American College of Obstetricians and Gynecologists, encourage the use of the Apgar score only for its original intent [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Apgar score was originally intended to assess the condition of newborns immediately after birth and to measure the response to resuscitations [ 3 ]. However, the Apgar score, particularly the five-minute Apgar score, is often used in outcome studies, as it provides useful clinical information about the fetal-to-neonatal transition [ 4 , 5 , 6 ], although some professional associations, such as the American Academy of Pediatrics and the American College of Obstetricians and Gynecologists, encourage the use of the Apgar score only for its original intent [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another way, if only children with Apgar scores of below normal range are considered, only two percent of livebirths will be included, and the vast majority of births will be grouped together, implicating the presence of similar risks between them, which might not be true. Despite this, however, only limited studies have attempted to account for this large segment of the population when analyzing the risks associated with five-minute Apgar scores [ 5 ]. Therefore, this study aimed to evaluate the association of the five-minute Apgar score and neurodevelopmental outcomes in children by taking the entire range of Apgar scores into account.…”
Section: Introductionmentioning
confidence: 99%
“…In the < 20 age group, the 1st minute mean APGAR score (6.91 ± 0.69) was signi cantly lower than that in the other age groups (p < 0.001). While neonatal NICU admission rates were higher in the < 20 age group (7.1%) than in the other two groups (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)4.49% and > 35, 4.20%), there was no signi cant difference (p = 0.12).…”
Section: Resultsmentioning
confidence: 88%
“…Although APGAR scores are used as a physiological indicator of how well the newborn adapts to the external environment [30], many factors such as gestational age, low birth weight, congenital anomaly, trauma, and infection can affect the [31]. Benage et al showed that a diet high in iron tablets, nutrients, and folic acid improves the overall health of Syrian refugee women, and therefore pregnancy outcomes [24].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of newborn outcomes, in our study, the mean birth weight was 3.151 g, and the 1st and 5th minute APGAR scores were 7.06 and 8.92, respectively. Although APGAR scores are used as a physiological indicator of how well the newborn adapts to the external environment [ 25 ], many factors such as gestational age, low birth weight, congenital anomaly, trauma, and infection can affect the scores [ 26 ]. Iron deficiency and low hemoglobin levels can lead to low-grade chronic hypoxia, increasing the risks of LBW and preterm birth [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%